Determination of malathion and glufosinate-ammonium in palm oil mill effluent using high performance liquid chromatography - Mohd Fauzan, Abdullah (2012)
The analysis of palm oil mill effluent (POME) is carried for determination of organophosphorus pesticide (OPPs) concentration namely malathion and glufosinateammonium. The sample pesticide is taken at three palm oil mill effluent pond which is Felda Palm Industries Sdn Bhd - KKS Lepar Hilir, Kilang Sawit Felda Chini 2 and Kilang Sawit Felda Chini 3. As to confirm the aim of pesticide that discharge from the production mill, the analysis is carried by using High-Perfomance Liquid Chromatography (HPLC). The HPLC is used for the separation and detection of the malathion and glufosinate-ammonium in the palm oil mill effluent sample. It is expected that there is malathion and glufosinate-ammonium in the PONE. As the analyte presence in the sample, the concentration of it is obtained by plotting calibration curve. The area obtain by the POME chromatogram was compared with standard analyte as to get the individual concentration. As the result yield, all of the palm oil mill sampling site show the presence of the malathion and glufosinate-ammonium. But then, the identification of the concentration was due to the value of LOD and LOQ.